Textual deviation and coherence problems in the writings of Arab students at the University of Bahrain: sources and solutions - Qaddumi, Muhammad K.H. (1995)
The present study compares the writings of a group of Arab students at the University of Bahrain in both Arabic and English. The main purpose is to investigate possible sources and solutions to the problem of textual incoherence and deviation. To this end, four hundred and sixty composition papers have been reviewed and thirty texts were analyzed in both languages to discover possible interference at the linguistic, cultural and rhetorical levels.